Restructuring of innovation policy based on global experience of formation of national innovation systems - Крикун, Юлія (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
The article studies the rating of the Global Innovation Index and the index of competitiveness of Ukraine; researches the experience of formation of national innovation systems; determines governmental policies, aimed at creating an enabling environment in the country to support innovations. The study offers basic positions, which will facilitate the integration of innovation in the scientific and technological world.